Studi Alokasi Anggaran Pendidikan Dasar Sembilan Tahun di Provinsi Jawa Barat - Harjoko Sangganagara (Jurnal Administrasi Pendidikan Indonesia, 2022)
The relatively small budget allocation of basic education in the West Java Province becomes a problem for improving the quality of based basic education as normatively stated in some documents of local development plans and regulations. Effective implementation of the policy is needed for improving basic education quality. From those points of view, there are some research questions : how about the financing ability of the government, what is the priority of educational budget allocation, how to use the budget, what is the result of the implementation of budget allocation policy and what is the impact of budget allocation policy implementation for improving the educational quality.The study was conducted through observing the process of educational budget allocation policy; the implementation of the policy; the achievement of basic education quality, in the use of using interview, library research and observation method. The method of post policy analysis was used to analyze the phenomenon of budget allocation policy in West Java Province. The result showed that the performance of the government of the West Java Province in implementing policy had been matched according to the principles of proportionality, efficiency and accountability but was not effective yet. The conclusion is that the result of budget allocation policy had relatively improved the quality of basic education.The recommendation is that more budgets must be given to basic education and budget allocation needs some priorities especially in providing school infrastructures, qualified teachers and personal cost. Meanwhile, some programs must be sharpened into quality improvement direction. Role sharing between national and local government needs to be continued until the compulsory education is accomplished.